PERANCANGAN DAN PENERAPAN SISTEM E-COMMERCE PADA PO KING’S STORE PONTIANAK - Riyadi Iskandar; Kartono Kartono; Dony Susanto (LPPM Universitas Widya Dharma Pontianak, 2021)
The development of computer and internet technology is now more rapidly. Many companies are beginning to switch to applying technology to every area of work. PO King’S Store needs to need an online sales information system in terms of sales service to customers. Based on this the researcher designing an online sales system that can improve the sales process. With the design of online sales system, it will facilitate customers in ordering products and get information about the product in detail. Researchers use descriptive research method. While the data collection method used is interview method, observation and literature study. System design techniques used in research is object-oriented techniques with modeling Unified Modeling Language (UML). System design application used is using database design with MySQL, programming language used is CSS, JavaScript, Hypertext Preprocessor (PHP) and Hypertext Markup Language (HTML). Editor used is Notepad ++. The end result of this research is in the form of an online sales system design that can assist in facilitating customers to order goods that can be accessed online. The results of this study are expected to improve service sales of goods, useful and satisfactory for customers, as well as the management in the PO King’S Store. Keywords: Designing, Information Systems, Sales, Online, Web